ANALISIS YURIDIS PERJANJIAN JUAL BELI BENDA VIRTUAL DALAM GAME ONLINE DOTA 2 OLEH ANAK YANG BELUM DEWASA MELALUI MEDIA INTERNET - DWIKI CAESAR RAHMANA NIM. A1011151144 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac In this thesis, the author raises the issue of Juridical Analysis of the Sale and Purchase Agreement of Virtual Objects in the Online Game of Dota 2 by Children who are not yet proficient through Internet Media in Pontianak City. Agreements with unqualified children are made by accessing the web page or media or software provided, containing clauses or agreements made by the first party (the seller) and the other party (the buyer) by simply pressing the button provided as a sign of approval for the contents of the agreement. already exists, without the need for a signature like a general agreement, but using an electronic signature or digital signature. So that the parties do not need to meet in person to enter into an agreement. In the online game DOTA 2, there is a system of buying and selling virtual objects which are generally the same as other online games, the online game DOTA 2 that plays not only adults but children who are underage also play which in practice is in the children's field. also conduct buying and selling virtual objects through internet media, namely the website www.itemku.com. The formulation of the problem in this study is